Analysis of Regional Fixed Asset Management in Supporting Regional Original Income (PAD) in Central Lombok Regency 2013-2022 - Laily Rohmi Alfiana; M. Irwan; Siti Fatimah (Future Techno-Science, 2025)
This study aims to analyze the management of regional fixed assets in supporting Regional Original Income (PAD) in Central Lombok Regency during the period 2013–2022. The main focus of this study is to measure the contribution, effectiveness, and efficiency of fixed asset utilization and examine how fixed asset management is implemented. The method used is quantitative descriptive with contribution analysis techniques, effectiveness ratios, and efficiency ratios to Regional Original Income based on budget realization report data and fixed asset balance sheets. The results of the study indicate that the contribution of revenue from fixed asset utilization to PAD in 2013-2022 has an average result of very low, still relatively low and fluctuating. The level of effectiveness of fixed asset utilization revenue in 2013-2022 with an average result of less effective and the efficiency of fixed asset utilization revenue in 2013-2022 has an average result of quite efficient. The level of effectiveness and efficiency of asset utilization is also not optimal, due to the low quality of management, minimal maintenance, and lack of accuracy in asset inventory. Some of the problems found include assets that do not have clear legality, recording that is not in accordance with the classification, and utilization that is not yet optimal. Therefore, a more structured, transparent, and accountable fixed asset management strategy is needed to increase its contribution to PAD and support regional fiscal independence.